2017
DOI: 10.1186/s13049-017-0410-0
|View full text |Cite
|
Sign up to set email alerts
|

Mortality due to traumatic spinal cord injuries in Europe: a cross-sectional and pooled analysis of population-wide data from 22 countries

Abstract: BackgroundTraumatic spinal cord injuries (TSCI) pose a significant burden globally, while existing epidemiological data–especially on population mortality–are limited. The aim of this study was to calculate the age-standardized population mortality rates attributable to TSCI in 22 European countries, along with the pooled age-standardized mortality rate attributable to TSCI in Europe.MethodsA descriptive cross-sectional epidemiological study was conducted. Crude and age-standardized mortality rates attributabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 21 publications
5
14
0
Order By: Relevance
“…The mortality rate in our series was low (2.27%) and was related to older age, higher cervical levels of injury and poor functionality, as in other studies [ 11 , 25 ].…”
Section: Discussionsupporting
confidence: 76%
“…The mortality rate in our series was low (2.27%) and was related to older age, higher cervical levels of injury and poor functionality, as in other studies [ 11 , 25 ].…”
Section: Discussionsupporting
confidence: 76%
“…A study by Ghaem et al showed that trauma-related mortality was higher in patients older than 55 years (17). Besides, Majdan et al argued that the TSCIrelated mortality rate was higher in patients older than 65 years (18), which is in agreement with our study. Interestingly, the prevalence of TSCI is significantly higher among young adults, and differences between age groups may be due to differences in methodology, socioeconomic status, culture, and area of living.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the results showed that the mortality rate was significantly higher in patients with cervical spine and spinal cord injuries. Majdan et al reported that the most common cause of death in trauma patients was cervical injuries (66% in males vs. 55% in females), followed by lumbar injuries (19% in males vs. 26% in females) (18). A study by Majdan et al in Australia showed that the most common level of injury was cervical damage, which complied with our study.…”
Section: Discussionsupporting
confidence: 91%
“…Spinal cord injury (Sci) is a serious neurological injury caused by traffic accidents, falls, or violence-associated injuries, resulting in heavy financial and psychosocial burdens on patients and society (1)(2)(3)(4). Sci can lead to impaired sensory and motor functions, autonomic nervous dysfunction and altered mental health (1).…”
Section: Introductionmentioning
confidence: 99%